(x-y)^2+(x+y)(x-y) 其中 X =3 Y=-1
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 00:34:42
(x-y)^2+(x+y)(x-y)其中X=3Y=-1(x-y)^2+(x+y)(x-y)其中X=3Y=-1(x-y)^2+(x+y)(x-y)其中X=3Y=-1(x-y)^2+(x+y)(x-y)=
(x-y)^2+(x+y)(x-y) 其中 X =3 Y=-1
(x-y)^2+(x+y)(x-y) 其中 X =3 Y=-1
(x-y)^2+(x+y)(x-y) 其中 X =3 Y=-1
(x-y)^2+(x+y)(x-y)
=(x-y)(x-y+x+y)
=(x-y)2x
x=3 y=-1 x-y=3+1=4
原式=4×2×3=24
(x-y)^2+(x+y)(x-y)
=(x-y)(x-y+x+y)
=2x(x-y)
=2*3(3+1)
=24
x-y/x-x+y/y-(x+y)(x-y)/y² y/x=2
(x+3y)²-2(x-y)(x+y)+(x+y)²其x=0.5,y=-2
化简y(x+y)+(x+y)(x-y)-x^2
(x+y)(x-y)-(x-y)^2如题 (x+y)(x-y)-(x-y)^2
先化简 再求值 (2x-y)(y+x)-(x-2y)(2y+x)-(-3y+x)^2其(√x+1)+y^2+4=-4y
【2(x-y)(x-y)(x-y)-8(x-y)(x-y)(x+y)+6y(x-y)(x-y)]/2(x-y)(x-y)
因式分解x(x+y)(x-y)-x(x+y)^2
{(x,y) |x|+|y|
x>y?x:y
[(x-y)^2-(x+2y)(x-2y)]/y
计算:y-x分之x+y+x-y分之y-y-x分之2x-y
x^2(x-y)+(y-x)
x(x-y)2-(y-x)3
【(x-y)^2+(x+y)(x-y)】除以 2x
[(x-y)²+(x+y)(x-y)]除以2x
[2/3x-2/x+y(x+y/3x-x-y)]/x-y/x
化简:{2/3x-2/(x+y)[(x+y)/3x-x-y]}/(x+y)/x
计算2/3x-2/x+y(x+y/3x-x-y)/x-y/x